ANALISIS PENYAJIAN LAPORAN KEUANGAN PADA PT.MULTISARANA BAHTERAMANDIRI BERDASARKAN PSAK NO.1 DAN NO.2 - Darmawan, Mizaco Ofayda; Poputra, Agus Toni; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Statement of Financial Accounting Standards (SFAS) number 1 and 2 states that financial statements should present fairly the financial position, financial performance, changes in equity and cash flow. Companies to implement SFAS correctly with the required disclosures in the Notes to the Financial Statements. Objects in this research is PT.Multisarana Bahteramandiri. The purpose of this study is to analyze the financial statement presentation PT.Multisarana Bahteramandiri under SFAS Number 1 and 2. The method used is descriptive analysis method is an analytical tool that compares two different aspects of theory and practice that need to be met in order to know the difference, as far as what the difference is. Results of the analysis of these data showed that PT.Multisarana Bahteraamandiri not fully implemented SFAS number 1 and 2 in the company's financial statement presentation. Because the company only present a statements of financial position, income statement, cash flow statement, as well as company-specific notes. The company also not disclose a statement of compliance with the Statement of Financial Accounting Standards (SFAS) number 1 and 2 in the notes to financial statements.